Prevalence of species-specific candidiasis and status of oral hygiene and dentition among diabetic patients: A hospital-based study - Ritu Duggal; Ravinder Goswami; Immaculata Xess; Isha Duggal; Aditya Talwar; Vijay Prakash Mathur (Wolters Kluwer Medknow Publications, 2021)
Objective: The study was undertaken to estimate the species-specific prevalence of oral candidiasis in diabetic individuals in India, and further find the relationship of oral carriage of Candida in diabetes with degree of diabetic control, duration of disease, type of diabetes and its effect on the status of oral hygiene status and decayed, missing and filled teeth (DMFT) score. Methodology: The prospective cross-sectional study involved 900 individuals (470 diabetic and 430 non-diabetic) visiting a tertiary care hospital. Informed consent was obtained from all the individuals participating in the study. The demographic details, medical history and oral cavity examination were recorded in a specially designed proforma. Swabs were taken for microbiological evaluation for specific prevalence of Candida. Results: The overall prevalence of Candida in diabetics was 22.1% as compared to 9.7% in non-diabetic individuals. However, among the type 1 and type 2 diabetics, the prevalence of Candida was equally distributed as 22.6% and 20.8%, respectively. C. albicans was the most common species (97.1%), while isolated cases of other species like C. rugosa, C. tropicalis, C. glabrata were also observed. The individuals with higher glycaemic score (HbA1c >7) showed higher prevalence of oral candidiasis. Oral hygiene status was observed to be lower among diabetics as compared to non-diabetic individuals. Conclusion: Oral candidiasis was more prevalent in diabetic patients, and C. albicans was the most common species. The diabetics also showed higher mean DMFT with lower oral hygiene status as compared to non-diabetic individuals.